The Meat Freshness Monitoring System Using the Smart RFID Tag. (9th July 2014) - Eom, Ki-Hwan; Hyun, Kyo-Hwan; Lin, Sen; Kim, Joo-Woong
Abstract : This paper proposes a monitoring system for meat freshness and use-by date, based on the smart RFID (radio frequency identification) tag. Freshness can be checked by various factors, such as the presence of microorganisms, bacteria, and gases. This paper focuses on detecting the temperature, humidity, and the gases released by meat. We analyzed the factors affecting the freshness of meat and decided to use a gas sensor as the main detection method. We use temperature sensor and humidity sensor as auxiliary sensors to get the food poisoning index. The proposed system consists of an RFID tag, temperature sensor, humidity sensor, gas sensor, reader, and server. By comparing the temperature, humidity, and gas concentration of the meat storage environment, we can get the relationship between meat freshness and the sensor signal. This monitoring system can show the meat freshness at four distinct grades: High, Medium, Low, and Spoilage. In order to confirm the usefulness of the proposed system, we performed experiments on pork. With the smart RFID tag, we successfully estimated the freshness of the meat.